2017
DOI: 10.1155/2017/2168767
|View full text |Cite
|
Sign up to set email alerts
|

miR-217 Is a Useful Diagnostic Biomarker and Regulates Human Podocyte Cells Apoptosis via Targeting TNFSF11 in Membranous Nephropathy

Abstract: Background MicroRNAs have recently been verified as useful diagnostic biomarkers in various diseases. In this study, we investigated whether miR-217 is a useful diagnostic biomarker and the possible pathological mechanism of miR-217 in this disease. Methods Patients with focal segmental glomerulosclerosis (FSGS), membranous nephropathy (MN), and diabetic nephropathy (DN) and control patients were enrolled in this study. The miR-217 inhibitor and mimics were transfected into human podocyte cells to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…By modulating human podocyte apoptosis through targeting TNFSF11, miR‐217 has been reported as a useful diagnostic biomarker in membranous nephropathy (Li et al., ). Besides, miR‐217 is widely implicated in many diseases, functioning as a potential tumour suppressor in osteosarcoma and a diagnostic and prognostic biomarker for chronic pancreatitis and pancreatic ductal adenocarcinoma (Vychytilova‐Faltejskova et al., ; Wei et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By modulating human podocyte apoptosis through targeting TNFSF11, miR‐217 has been reported as a useful diagnostic biomarker in membranous nephropathy (Li et al., ). Besides, miR‐217 is widely implicated in many diseases, functioning as a potential tumour suppressor in osteosarcoma and a diagnostic and prognostic biomarker for chronic pancreatitis and pancreatic ductal adenocarcinoma (Vychytilova‐Faltejskova et al., ; Wei et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of non‐coding RNAs that negatively regulate gene expression at the post‐transcriptional level, participating in many biological and pathological processes (Bernardo, Ooi, Lin, & McMullen, ). It has been reported that miR‐217 was significantly down‐regulated in the renal tissue and plasma of membranous nephropathy and down‐regulation of miR‐217 induced human podocyte cells apoptosis (Li, Liu, Xue, Zhou, & Peng, ). Through bioinformatics, the complementary base pairs between miR‐217 and TLR4 were found, suggesting potential interaction between them and some influence on podocyte apoptosis and membranous nephropathy progression.…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed miRNAs has been found to be commonly presented in human diseases, including MN [28]. The circulating miRNAs associated with a specific pathophysiological state have been demonstrated as the useful diagnostic biomarkers for MN, such as miR-217 [11]. In addition, recent studies reported that miR-186 was significantly down-regulated in renal tissue from MN patients that contributed to podocytes apoptosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies showed a close connection between abnormal miRNAs and MN progression. For example, the relative expression of miR-217 was significantly downregulated in the tissue and plasma of MN patients and the receiver operating characteristic (ROC) curve analysis indicated that miR-217 might serve as a useful diagnostic biomarker for MN [11]. Both miR-217 and miR-186 were reported to be related with podocytes apoptosis in MN [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, better understanding of the potential mechanisms on PDLSCs differentiation could be helpful for the treatment of periodontitis. diseases, such as chronic heart failure (Nie et al, 2018), membranous nephropathy (Li et al, 2017), neuropathic pain (Jiang et al, 2019) and malignant tumor (Zhu et al, 2016, Nishioka et al, 2014, Zhao et al, 2010. However, the role of miR-217 on the osteogenesis differentiation of PDLSCs is unknown.…”
Section: Introductionmentioning
confidence: 99%